PROMOTING URBAN TOURISM THROUGH CITY BRANDING - DORINA NIȚĂ (Annals of the University of Petrosani: Economics)
Nowadays we are witnessing some sort of paradox with regards to the tourism practiced at the level of the big cities of the world. Regardless of the purpose of the journey: visiting historic landmarks, for pleasure and relaxation, on business, etc., tourists have become very irritating for the people residing in these cities and thus enforcing measures that would limit the number of tourists. At the opposite end, there are other urban destinations which, aware of the importance of a town’s reputation in attracting tourists and of the advantages, especially economic ones, generated by tourism, seek to build and capitalize on the most representative town brand. In this paper we shall analyse the way a Romanian town within Hunedoara County has built its branding strategy around a historic landmark which is Deva fortress.